Role of Nd3+ concentration on the microstructure and scintillation behaviour of langbeinite sulphate (vol 284, 128997, 2021) - Poornima, Velswamy; Mohan, Subramaniam; Uma, Tiruchirappalli Sivagnanam (Materials Letters, 2021)

Role of Nd3+ concentration on the microstructure and scintillation behaviour of langbeinite sulphate - Poornima, Velswamy; Mohan, Subramaniam; Uma, Tiruchirappalli Sivagnanam (Materials Letters, 2021)
Langebeinite (K2Ca2(SO4)(3)) ceramics doped with increasing concentrations of Nd3+ ions (0.01-0.04 mol%) was prepared by wet chemical precipitation and calcination at 800 degrees C. Thermal studies revealed high temperature stability of the phosphors. UV-VIS-NIR spectroscopic analysis of phosphors reveal strong absorption peaks representing f -> f transitions. Direct bandgap derived from Kubelka-Munk plot was found to be similar to 5.66 eV. FTIR studies reveal tetrahedral symmetry of the SO42 ions. SEM micrographs reveal the formation of phosphors with wide particle size distribution and elemental composition was analysed using EDX studies. Scintillation studies representing a single high intensity peak around 784 nm is ascribed to I-4(9/2) -> F-4(5/2) + H-2(9/2) transition. Langbeinite phosphor with 0.02 mol% of Nd3+ exhibited maximum emission intensity indicating optimal concentration for scintillation studies favouring the development of NIR emitting phosphors. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Langebeinites; Luminescence; Microstructure; Neodymium; Scintillation